O Barão da Caridade: a morte de Guilherme Studart e a invenção de uma vida exemplar (1856-1938) - Holanda Filho, Pedro (2018)
This dissertation discusses the historicity of charity as a form of sensibility through the experience of death based on the actions of Guilherme Chambly Studart’s (1856-1938). Known as the Barão de Studart, he was a relevant player in the political and intellectual landscape in Ceará between the late XIXth and early XXth century. Physician, historian, intellectual, Catholic, Studart was a founder and member of many institutions such as the Historical Institute of Ceará and the São Vicente de Paulo Society (whose experience resulted in the title of baron by the Catholic Church). Concerned about death throughout his whole life, Studart created a self-image of an exemplary man by practicing charity and producing his own personal archive, which framed him as a charitable, intellectual, devout and patriot man. I argue, based on Studart’s life reveals, that charity before death was a component of social relationships in the studied period. The argument is based on the study of wills, documents meant for the exhibition of emotions in which charity played a major role. This reflection focuses on the history of sensibilities thinking revolving around death, which is definitive of the time and demonstrated a way of acting, thinking and being. Studart’s personal archive, in this sense, is fruitful, containing with photos, personal documents, letters, and books. With his will, the archive is understood as an autobiographic act. Therefore, this dissertation follows Guilherme Studart’s life, seeing him as a person who practiced charity in his time, with no interest in ending poverty, but doing palliative actions which gave momentary comfort, justifying the wealth of some and showing that those who practice charity were essential cogs in the wheel of society.